Airborne pollutants from landfills and their health effects on scavengers and nearby communities: A scoping review - Damayanty, Sri; Saleh, Lalu Muhammad; Mallongi, Anwar; Noor, Nur Nasry; Daud, Anwar; Darmawansyah, Darmawansyah (Edelweiss Applied Science and Technology, 2025)
Landfills are major sources of airborne pollutants such as H₂S, NH₃, volatile organic compounds (VOCs), particulate matter, and bioaerosols, which threaten both environmental and human health. This scoping review aimed to map landfill-related airborne pollutants, assess their health impacts, and identify research gaps for future directions. A comprehensive search was conducted in Scopus, PubMed, Web of Science, and ScienceDirect for studies published between 2020 and August 2025. Studies were screened and charted, resulting in 18 articles included. Data were synthesized thematically into four domains: types of airborne pollutants, health effects, methodological innovations, and research gaps. The review identified diverse pollutants, with H₂S, NH₃, VOCs, PM, and microbial bioaerosols most frequently reported. These were associated with respiratory dysfunction, cardiovascular risks, infectious diseases, and possible carcinogenic effects. Scavengers and marginalized communities consistently experienced higher exposures due to socioeconomic disadvantages and the absence of occupational safety measures. While methodological advances such as environmental monitoring and spatial modeling have improved understanding of pollutant dispersion, most studies relied on cross-sectional designs, lacked biomonitoring, and underrepresented vulnerable groups. Airborne pollutants from landfills represent a significant but under-researched environmental health challenge. Strengthening evidence requires longitudinal and biomarker-based studies focusing on vulnerable populations.